ANALISIS KOMPARATIF USAHATANI JAGUNG VARIETAS BISI 18 DAN VARIETAS PIONEER P27 GAJAH DI DESA REMBITAN KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Wiliya, Juli; Ibrahim, Ibrahim; Septiadi, Dudi (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2023)
This research aims to compare production costs, production quantities, income and farming efficiency of corn variety Bisi 18 and corn variety Pioneer P27 Gajah in Rembitan Village, Pujut District, Central Lombok Regency. This research uses a descriptive method. The unit of analysis is the Bisi 18 variety corn farming and Pioneer P27 Gajah corn variety in Rembitan Village, Pujut District, Central Lombok Regency. Determining the number of sample respondents for corn variety Bisi 18 and corn variety Pioneer P27 Gajah using